Design of student score application for assessing the most outstanding student at vocational high school - Abadi, Satria; Shukri Mat The, Kamarul; Huda, Miftachul; Hehsan, Aminudin; Nasir Ripin, Mohd.; Haron, Zulkifli; Hisyam Nor Muhamad, Nasrul; Rianto, Riki; Maseleno, Andino; Renaldo, Riki; Syarifudin, Ahmad (International Journal of Engineering and Technology, 2018)
Learning achievement is a representation of student success level in learning. In accordance with the rules that have been determined by Muhammadiyah Vocational High School (SMK) to know the student achievement, it is needed criteria to determine who will be selected to be the most outstanding student. The purpose of this study was to design the Student score Information System as a support in decision-making and daily operational purposes, and to compare the effectiveness and efficiency of data processing and presentation of information between existing systems and information systems to be proposed. In improving the development process that the author will develop Student Information System as a supporter in decision making using Visual Basic 6.0 programming language. Research conducted in this case was descriptive qualitative research by conducting survey on the object of research that is in Vocational High School (SMK) Muhammadiyah Pringsewu District by using data collecting technique there were observation, interview, and literature study. The conclusion of writing this research is expected that the new system can provide convenience to the parties involved in performing data processing quickly and accurately, and can store data safely to assist in the process of service to students and society generally.Â Â